Strategy Formulation and Implementation for PT Manufaktur to Survive and Begin Competing in The National Automotive Market - Adrian, Adrian; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2014)
Abstract. The development of national automotive industry especially in four-wheeled vehicle in the era of business adult. The stability of economic growth, increasing in urbanization, goverment policy that encouraged the production of low-emssion cars are some of the factors that underlying it. Unfortunately, not a local automotive company that dominate this industry, but the automotive company from Sakura’s country. However, through the passing emission test by Esemka Rajawali and Bima that are produced by national vocational schools students, give a new hope and colour in the competition of national automotive industry. PT. Manufaktur as the official local automotive company that producing Esemka cars is expected to compete with Japan automotive companies that has already long dominated the national automotive industry. As the newcomer in the national automotive industry, PT. Manufaktur facing the heavy competition. Some of the challenges such as: lack of public’s confidence for local products, the quality of technology, human resources and the capital owned still far compared to competitors. Fishbone diagram conclude that the main problem of company is losing in competition. Therefore, to deal with this situation, company needs to apply the right strategies in order to survive and compete in this industry. The study focus on designing the strategy formulation and its implementation that will be used by company. The method used in this study is Strategic Management. Starting from analyzing the external (opportunities and threats) through general analysis, five porter forces and competitior analysis and internal (weaknesses and strengths) environment through resource and capabilities analysis, and later called as situation analysis. Then, conducted the strategic factor analysis summary (SFAS) and make the alternative strategies using TOWS analysis. The next step is reviewing on mission and objective which are based on SFAS and TOWS analysis. The resulted of alternative strategies then formulated on a corporate level, business level and functional level. After that, the final stage is executing or implementation stage, which is a step to apply and implement the strategies accordance with the pattern of time that has been determined, how are the details of its activity and which divisions are responsible for that strategy.The result is, PT. Manufaktur need to make efficiency or retrenchment strategy for its every business units and captive to government. Cost leadership strategy and strategy alliance become a guideline for business level. In functional level, some strategies that should be done such as: the construction of a new bigger plant, issued a new variants (Low Cost Green Car, Low Multi Purposes Vehicle and Gas-Fuelled cars type), loan strategy for the funding of new plant, promoting company’s brand, optimize the broad networking and others.Keywords: Automotive industry, Esemka cars, Fishbone, Strategic Management